Transient Elevation of the Ipsilateral Hemidiaphragm Associated with Pneumonia - Andrew Fretzayas; Maria Moustaki; Polyxeni Nicolaidou; Efthimia Alexopoulou; Konstantinos N Priftis (Canadian Respiratory Journal)
Seventeen children with lobar or segmental pneumonia and ispilateral elevation of the diaphragm are described. These children did not differ significantly with respect to clinical and laboratory findings from their counterparts with pneumonia but without elevation of the hemidiaphragm. The elevation was transient and resolved by the time the repeat chest x-ray was taken six to eight weeks later.